Elemen-Elemen Black Comedy dalam Film The Menu - Surur, Misbahus - (Rekam, 2024)
In the film The Menu, culinary dishes are used to peel off the social disgrace and sins of the elite without them ever suspecting before. This research aims to find out how culinary offerings and the arrogance of elite class dining wrapped in black comedy are represented in the film The Menu. The research method used is qualitative-descriptive using watch-listen-note data collection techniques. The researcher watched the film, paid attention to the details of each scene, transcribed the dialogue, and recorded every conversation and scene related to important culinary topics wrapped in black comedy in the film. Meanwhile, data analysis techniques use the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. In the analysis, the researcher identified the data, sorted and classified the data, and finally interpreted it using gastronomic theory as a guide. Data sources include words, phrases and sentences in the film The Menu. From this research it was found that the culinary delights in the film The Menu are presented in 7 culinary stages: The Island, Breadless Bread Plate, Memory, The Mess, Palate Cleanser, Man's Folly and the dessert S'mur. And the arrogance of elite class dining wrapped in black comedy is depicted in several scenes of their teasing questions, both to the chef and his assistants and to the culinary offerings, as well as the answers of the chef and the crew themselves, from the time the customers entered Hawthorn Island until the time the seven dishes were served.